Clinical and histopathological characteristics of prostate cancer in Erbil city/ Iraq - Shakir Mola ahmed, Narin; Rahman Sulaiman, Luqman (Zanco Journal of Medical Sciences (ZJMS), 2024)
Background and objective: Prostate cancer is the third most common cancer in men in Iraq. We aimed to study the epidemiology, clinical and histopathological characteristics of prostate cancer in Erbil city. Methods: The research was performed retrospectively at Nanakali Teaching Hospital and the Oncology Department of Rizgary Teaching Hospital in Erbil city, covering the period from 2016 to 2021. Comprising 212 people diagnosed with prostate cancer. Results: The median age of the patients was 71 years. The proportion of patients who present with urinary tract symptoms, no symptoms and other were 81.6%, 4.7% and 13.7% respectively. Two hundred eight prostate cancer patients with available histopathological data had adenocarcinoma and two patients had neuroendocrine carcinoma and one patient had urothelial cancer. The proportion of patients with high grade tumor, intermediate and low grade were 61%, 29% and 10% respectively. While, the percentage of patients with TPSA level > 20 ng/ml, TPSA >100 ng/ml were 80% and 35% respectively. Furthermore, the proportion of patients with stage IV, III, II and I were 62.7%, 17.9%, 17.9% and 1.4% respectively. And, the percentage of high-risk groups, intermediate and low risk were 90.1%, 8% and 1.9% respectively. After correlation of TPSA with stage of disease and grade of tumor there was statistically positive correlation between them. Conclusion: Patients diagnosed with prostate cancer in our region are more likely to belong to the high-risk category, exhibiting aggressive disease and advanced stage at the time of diagnosis. Nevertheless, they exhibit comparable demography and epidemiology as shown in the recent international literature about the global population and the Middle East region.